Sand Mining Environmental Impacts and Selected Case Studies - Padmalal, D.; Maya, K. (Environmental Science and Engineering, 2014)
This book addresses most of the environmental impacts of sand mining from small rivers. The problems and solutions addressed in this book are applicable to all rivers that drain through densely populated tropical coasts undergoing rapid economic growth. Many rivers in the world are drastically being altered to levels often beyond their natural resilience capability. Among the different types of human interventions, mining of sand and gravel is the most disastrous one, as the activity threatens the very existence of river ecosystems. A better understanding of sand budgets is necessary if the problems of river and coastal environments are to be solved.